DOI: 10.11606/t.12.2018.tde-12062018-121650
|View full text |Cite
|
Sign up to set email alerts
|

Managing collaborative R&D with different types of knowledge sources.

Abstract: Yu inspired my first steps in academia. His skill in helping students develop a critical thinking is inspiring. He had a great influence on my decision to follow the academic path. The course Innovation Management in Products and Processes that he gave together with Prof. Dr. Paulo Tromboni was of great interest and was one of the first influences that helped to define the focus on Innovation Studies in my PhD and my research career. With Prof. Dr. Paulo Feldman, I had the chance to write a paper after a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 55 publications
(133 reference statements)
0
11
0
1
Order By: Relevance
“…Primary data, collected by Barbosa [22] and available at Barbosa et al [36], was used. Considering the scope of the current study, only the selected data from [36] was adapted while reducing the scope of the framework of Barbosa [22]. The framework, adopted in the current study is shown in the figure 5.…”
Section: A Methodology and Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Primary data, collected by Barbosa [22] and available at Barbosa et al [36], was used. Considering the scope of the current study, only the selected data from [36] was adapted while reducing the scope of the framework of Barbosa [22]. The framework, adopted in the current study is shown in the figure 5.…”
Section: A Methodology and Frameworkmentioning
confidence: 99%
“…Collaborative projects face many challenges that a general Project Management approach doesn't support [22, p. 47]. The performance of project in terms of cost (budget), schedule (time) and technical quality are the key attributes of successful project management and thus were the three constructs of the project management performance (PM g ) in the study [22]. The overall performance was considered as ''R&D Output'', discussed in the following section.…”
Section: ) Project Management Performance (Pm G )mentioning
confidence: 99%
See 3 more Smart Citations